2018
DOI: 10.1111/1471-0528.15110
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric fistula: a paradigm shift is needed in research and prevention

Abstract: Please cite this paper as: Letchworth P, MacLaren E, Duffy S. Obstetric fistula: a paradigm shift is needed in research and prevention. BJOG 2018;125:925-928.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Also, though prevention is key, treating those that already have fistula remains of great importance especially considering the enormous impact of OF on the affected women. Fortunately, after the launch of the global campaign to end fistula in 2003, much progress has been made in improving the treatment of OF patients, but the best strategy for OF prevention still remains a difficult topic [66][67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…Also, though prevention is key, treating those that already have fistula remains of great importance especially considering the enormous impact of OF on the affected women. Fortunately, after the launch of the global campaign to end fistula in 2003, much progress has been made in improving the treatment of OF patients, but the best strategy for OF prevention still remains a difficult topic [66][67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…Among patients who have undergone IPAA for UC, we found that bowel obstructions could develop after CS, and fecal incontinence and an increased stool frequency could develop, even after CS, according to this analysis. In the VD group, we found one case of vaginal fistula after delivery, although the association between VD and fistulizing is unclear because injuries of the soft parturient canal can commonly develop during delivery [26,27]. The remaining three patients with VD had no problems after delivery.…”
Section: Discussionmentioning
confidence: 78%
“… 10 , 11 Despite such efforts, obstetric fistula still compromises the well-being of affected women in all dimensions of their health. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…10,11 Despite such efforts, obstetric fistula still compromises the well-being of affected women in all dimensions of their health. 12,13 Many women with obstetric fistulas experience varying degrees of social stigma that can prevent them from seeking care early. 5 In addition, lack of sexual and reproductive health knowledge, or cultural inhibitions to discuss these topics, lead a woman to accept these conditions as normal postpartum healing rather than seeking care.…”
Section: Introductionmentioning
confidence: 99%